Pengaruh Pemberian Jus Semangka Merah Terhadap Tekanan Darah pada Dewasa Akhir di Kelurahan Mahawu Lingkungan VII - Nurlela Hi Baco; Agust A. Laya; Mohammad Reza Buhang (Universitas Muhamadiyah Manado, 2024)
Late adulthood is an advance stage of the life process characterised by a decline in the body’s ability to adapt to environmental stress. A person who has entered late adulthood will experience many declines including a decrese in physical and biological conditions. Hypertension is a disorder of the circulatory system that causes an increase in blood pressure above normal values. One of the non-pharmacological treatments for hypertension is complementary therapy by consuming red watermelon juice, which contains potassium and magnesium that has an effect in helping to lower blood pressure. The purpose of this research was to find out whether there is an effect of giving red watermelon juice on blood pressure in late adults in Mahawu Village, Neighborhood VII. This research is an experimental research design with One Group pretest-posttest design. The sample amounted to 15 people who had previously measured their blood pressure using a sphygmomanometer. Furthermore, the data that has been collected is tested for data normality. The hypothesis was tested with the Wilcoxon test to determine the decrease in blood pressure of respondents with significance level (α) of 0,05. The Wilcoxon statistical test results showed the ρ value of pre-post = 0,001. This ρ value is < α = 0,05. The conclusion of this research is that there is an effect of giving red watermelon juice on blood pressure in late adults in Mahawu Village, Neighborhood VII. It is expected that this research can increase knowledge that is useful for respondents to maintain blood pressure within normal limits..